Servant Leadership and Work Engagement among Generation Z Employees: Evidence from Indonesia's Digital Creative Industry - Muhammad Yudha Prawira Negara; Harsono, Mugi (JURNAL MANAJEMEN MOTIVASI, 2026)
Work engagement is essential for organizational performance, yet its determinants among Generation Z employees remain underexplored. This study examines the effect of servant leadership on work engagement and the mediating roles of employee resilience, perceived organizational support, and trust in leader among Generation Z employees in Indonesia’s digital creative industry. Using a quantitative approach, data from 263 respondents were analyzed with PLS-SEM. The results indicate that servant leadership positively affects work engagement both directly and indirectly through the three mediators. These findings highlight the importance of servant leadership in fostering employee engagement by strengthening personal, organizational, and relational resources.